Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г

Раздел:

Номер №243

Упростите выражение:
а)
$ab + \frac{ab}{a + b}(\frac{a + b}{a - b} - a - b)$
;
б)
$(\frac{y^2 - xy}{x^2 + xy} - xy + y^2) * \frac{x}{x - y} + \frac{y}{x + y}$
;
в)
$(\frac{1}{(2a - b)^2} + \frac{2}{4a^2 - b^2} + \frac{1}{(2a + b)^2}) * \frac{4a^2 + 4ab + b^2}{16a}$
;
г)
$\frac{4c^2}{(c - 2)^4} : (\frac{1}{(c + 2)^2} + \frac{1}{(c - 2)^2} + \frac{2}{c^2 - 4}).$

Решение а

$ab + \frac{ab}{a + b}(\frac{a + b}{a - b} - a - b) = ab + \frac{ab}{a + b} * (a + b) * (\frac{1}{a - b} - 1) = ab + ab(\frac{1}{a - b} - 1) = ab(1 + \frac{1}{a - b} - 1) = \frac{ab}{a - b}$

Решение б

$(\frac{y^2 - xy}{x^2 + xy} - xy + y^2) * \frac{x}{x - y} + \frac{y}{x + y} = (\frac{y(y - x)}{x(x + y)} + y(y - x)) * \frac{x}{x - y} + \frac{y}{x + y} = y(y - x)(\frac{1}{x(x + y) + 1}) * \frac{x}{x - y} + \frac{y}{x + y} = -\frac{yx(1 + x(x + y))}{x(x + y)} + \frac{y}{x + y} = -\frac{y(1 + x(x + y))}{x + y} + \frac{y}{x + y} = \frac{y}{x + y}(-1 - x(x + y) + 1) = -\frac{xy(x + y)}{x + y} = -xy$

Решение в

$(\frac{1}{(2a - b)^2} + \frac{2}{4a^2 - b^2} + \frac{1}{(2a + b)^2}) * \frac{4a^2 + 4ab + b^2}{16a} = \frac{(2a + b)^2 + 2(4a^2 - b^2) + (2a - b)^2 + (2a - b)^2}{(2a - b)^2(2a + b)^2} * \frac{(2a + b)^2}{16a} = \frac{4a^2 + 4ab + b^2 + 8a^2 - 2b^2 + 4a^2 - 4ab + b^2}{16a(2a - b)^2} = \frac{16a^2}{16a(2a - b)^2} = \frac{a}{(2a - b)^2}$

Решение г

$\frac{4c^2}{(c - 2)^4} : (\frac{1}{(c + 2)^2} + \frac{1}{(c - 2)^2} + \frac{2}{c^2 - 4}) = \frac{4c^2}{(c - 2)^4} : (\frac{(с - 2)^2 + (c + 2)^2 + 2(c^2 - 4)}{(c + 2)^2(c - 2)^2}) = \frac{4c^2}{(c - 2)^4} * \frac{(c + 2)^2(c - 2)^2}{c^2 - 4c + 4 + c^2 + 4c + 4 + 2c^2 - 8} = \frac{4c^2(c + 2)^2}{(c - 2)^24c^2} = (\frac{c + 2}{c - 2})^2$